2017
DOI: 10.1108/jima-06-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Halal certification organizations in the United Kingdom

Abstract: Purpose The aim of this paper is to investigate the role that halal certification organisations (HCOs) play in the UK in assuring quality in halal cosmetics. Design/methodology/approach The study evaluates whether halal certification assures the quality of halal cosmetic products. This research evaluated the quality assurance systems of major UK HCOs, using a hypothetical product as a test vehicle. The investigation considered whether these organisations differ in their definition of “halal” and “halal cosme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 59 publications
(107 reference statements)
2
24
0
4
Order By: Relevance
“…Recently, the researchers and practitioners have given more attention to the "halalness" concept and factors that affect buying or consumption behavior of Muslim consumers (Wilson, 2014). However, most of the existing literature is focused on food and the halal issues of the cosmetic industry are relatively neglected (Abd Rahman et al, 2015;Annabi and Ibidanpo-Obe, 2017;Mohezar et al, 2016;Haque et al, 2018). Nevertheless, there is momentum in recent halal studies that attempt to explore halal issues related to other consumer products such as cosmetics.…”
Section: Cosmetics Purchase Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the researchers and practitioners have given more attention to the "halalness" concept and factors that affect buying or consumption behavior of Muslim consumers (Wilson, 2014). However, most of the existing literature is focused on food and the halal issues of the cosmetic industry are relatively neglected (Abd Rahman et al, 2015;Annabi and Ibidanpo-Obe, 2017;Mohezar et al, 2016;Haque et al, 2018). Nevertheless, there is momentum in recent halal studies that attempt to explore halal issues related to other consumer products such as cosmetics.…”
Section: Cosmetics Purchase Behaviormentioning
confidence: 99%
“…Muslim consumers are unique in the sense they need to abide with halal requirement as prescribed in Islamic teachings. According to Annabi and Ibidanpo-Obe (2017), Mohezar et al (2016), Saqib et al (2016) and Abd Rahman et al (2015), although halal cosmetics are a relatively minor issue compared to halal food, there is growing awareness of halal cosmetics and personal care products among Muslim consumers. Based on Abd Rahman et al (2015), consumers hold varying attitudes about halal between food and cosmetic products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, they highlighted that ASEAN countries have potential to harmonise the halal certification system because they understand the halal practices. Annabi and Ibidapo-Obe (2017) investigated the role of halal certification in assuring the quality of halal cosmetics and found that there is a failure to adopt holistic halal terminology. Ali and Suleiman.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study also points out the challenges faced by the adapted components. Annabi and Ibidapo-Obe (2017) through inductive qualitative and evaluative research method investigated how halal logo assures the quality of cosmetic products in UK. Ab Talib et al (2017) empirically suggested that halal food certificate implementation positively influences business performance.…”
Section: Jima 112mentioning
confidence: 99%